Evaluation of the transmission-blocking potential of Plasmodium vivax antigen Pvg37 using transgenic rodent parasites and clinical isolates - Zhang, Di; Zhao, Yan; Liu, Dongyan; Liu, Fei; Liu, Pengbo; Zhang, Biying; Wu, Zifang; Roobsoong, Wanlapa; Bantuchai, Sirasate; Thongpoon, Sataporn; Sripoorote, Piyarat; Wang, Meilian; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPlasmodium vivax is a major cause of malaria, particularly outside Africa, necessitating effective strategies for public health management. Transmission-blocking vaccines (TBVs) have shown the potential to inhibit malaria transmission by targeting antigens expressed in sexual-stage parasites. Pbg37, a conserved protein expressed in sexual stages from gametocyte to ookinete in the rodent parasite P. berghei, is a viable target for TBV development.Methods and findingsIn this study, we constructed a transgenic strain, TrPvg37Pb, expressing Pvg37 using the P. berghei ΔPbg37 strain. Initial findings demonstrated that the replacement of Pbg37 with the exogenous Pvg37 did not impact parasite growth or development. Notably, Pvg37 was expressed during the gametocyte to ookinete development and was associated with the plasmic membrane, similar to Pbg37. To evaluate the potential of Pvg37 as a TBV candidate, we synthesized two Pvg37 polypeptides and immunized rabbits to generate antibodies. In vitro experiments demonstrated that anti-Pvg37-P2 antibodies significantly inhibited the formation of male gametes and ookinetes in the transgenic TrPvg37Pb parasite. Additionally, in mosquito feeding assays, mosquitos feeding on TrPvg37Pb-infected mice passively transferred with anti-Pvg37-P2 antibodies showed a significant 80.2% decrease in oocyst density compared to the control group. Furthermore, in direct membrane feeding experiments using four clinical P. vivax isolates, the anti-Pvg37 antibodies significantly reduced oocyst density by 28.6–50.4%.ConclusionPvg37 is a promising candidate for P. vivax TBV development, deserving further research and optimization to enhance its immunogenicity and transmission-blocking activity.